2017
DOI: 10.3390/ijerph14010054
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Child Health of Internally Displaced Persons in Ukraine: A Qualitative Study

Abstract: Due to the conflict that started in spring 2014 in Eastern Ukraine, a total of 1.75 million internally displaced persons (IDPs) fled the area and have been registered in government-controlled areas of the country. This paper explores perceived health, barriers to access to healthcare, caring practices, food security, and overall financial situation of mothers and young children displaced by the conflict in Ukraine. This is a qualitative study, which collected data through semi-structured in-depth interviews wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…Qualitative research has shown how the legacy of this famine defines collective trauma that continues to perpetuate emotions, "inner states of horror", and survival-driven coping strategies on an intergenerational basis [7,8]. With respect to the current conflict in eastern Ukraine, evidence from a small qualitative study of internally displaced women and children has found that the armed conflict was reported as contributing to a "significant deterioration of perceived mental health" for most respondents, many of whom reporting experiencing anxiety, depression, and stress [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research has shown how the legacy of this famine defines collective trauma that continues to perpetuate emotions, "inner states of horror", and survival-driven coping strategies on an intergenerational basis [7,8]. With respect to the current conflict in eastern Ukraine, evidence from a small qualitative study of internally displaced women and children has found that the armed conflict was reported as contributing to a "significant deterioration of perceived mental health" for most respondents, many of whom reporting experiencing anxiety, depression, and stress [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is sometimes difficult to quantify SD as the types and meaning of somatic symptoms vary based on cultural beliefs and different health care contexts. In Ukraine, mental health is now recognized as playing an important role in overall well-being, although "attitudes toward people with mental illness can often be negative" [9,15]. Furthermore, somatic symptoms have not always been viewed through a biopsychosocial lens that recognizes the relationship between psychological stressors and physical ailments [16].…”
Section: Introductionmentioning
confidence: 99%
“…All associated with diseases for the low consumption of food sources of these nutrients in post-settlement refugees. Thus, nutritional status such as dyslipidemia, overweight and obesity, show the emergence of chronic non-degenerative diseases, as a result of consumption of low-cost and low nutritional value foods, instead of food such as fruits and vegetables, as a coping strategy to not suffer from hunger, and since these foods are more accessible 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, food security also includes respect for diversity and cultural foods. The condition of food insecurity occurs when one of these dimensions ceases to occur, and subjects the population to nutritional risks, such as refugees who do not have permanent access to food, or who do not have physical or economic access, or when food is prepared under inappropriate conditions in refugee households or camps, where resources are scarce [30][31][32][33][34][35][36][37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation